We can reduce negative paediatric appendicectomy rate: A cohort study. (November 2021) - Patel, Maitreyi; Thomas, Joel Joy; Sarwary, Haschmatullah
Abstract: Background: Appendicitis accounts for the most frequent surgical emergencies in childhood. The guidance from the Royal College of Surgeons and poor post operative outcomes in surgical patients during the pandemic, it would be expected that only children who had clinical signs of appendicitis and were unwell, would have undergone surgery. Hence, the negative appendicectomy rate during the pandemic should have decreased. The aim of this retrospective study was to assess the rate of negative appendicectomy amongst children <16 years of age during the first wave of the pandemic, from the announcement of the lockdown and determine if there was a true difference by comparing the rate with the same time period in 2019. Material and methods: Data of all children aged<16 years who were operated for appendicitis between 23/3/2020 and 30/06/2020 was collected retrospectively and compared with that of children operated during the same time period in 2019 for the rate of negative appendicectomy. Data were analysed using the two-tailed t -test for continuous data and χ2 or Fishers exact tests for categorical data with p value of <0.05 considered significant. Results: Twenty three paediatric patients presenting with acute appendicitis underwent appendicectomy during the COVID-19 pandemic and 35 patients during 2019. Overall 17.39% patients underwent laparoscopic appendicectomy in 2020 while 54.29% in 2019. The negative appendicectomy rate was zero during the pandemic while it was 17.14% in 2019. There was no difference in the median length of hospital stay during the two time periods. There was no significant difference in complication or re-admission rate. Conclusion: This study has the lowest reported incidence of negative appendicectomy rate during the pandemic following wider use of pre operative imaging and early senior involvement in decision making. The increased number of complicated appendicitis during the pandemic did not translate to worse clinical outcomes. Highlights: This study has the lowest reported incidence of negative appendicectomy rate during the pandemic. There was wider use of pre operative imaging and early senior involvement in decision making. There was a higher proportion of complicated appendicitis during the pandemic. However, this did not result in increased complications or re admission rate. It is possible to reduce negative paediatric appendicectomy rate by following the same lines of management.